2006
DOI: 10.1158/1078-0432.ccr-06-0114
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study ofIn vitroExpanded Natural Killer T Cells in Patients with Advanced and Recurrent Non–Small Cell Lung Cancer

Abstract: ) to test the safety, feasibility, and clinical response of this therapeutic strategy. Immunomonitoring was also done in all cases. Results: Six patients were enrolled in this study. No severe adverse events were observed during this study in any patients. After the first and second injection of activated Va24 NKT cells, an increased number of peripheral blood Va24 NKT cells was observed in two of three cases receiving a level 2 dose of activated Va24 NKT cells. The number of IFN-g-producing cells in periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
168
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(176 citation statements)
references
References 38 publications
6
168
1
1
Order By: Relevance
“…7,15,16,21,30,31 Although clinical trials examining NKT cell activation therapies in patients with advanced/recurrent disease have reported few cases of objective tumor regression, tumors tended to remain stable without the appearance of new metastatic foci. 15,[17][18][19][20]35 This suggests that NKT cell activation therapy might be more effective at targeting metastatic disease than primary tumors. Since primary breast cancer tumors are effectively treated by surgical resection, and disseminated metastasis remains the primary cause of mortality, 50 NKT cell activation therapy presents a promising therapeutic avenue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,15,16,21,30,31 Although clinical trials examining NKT cell activation therapies in patients with advanced/recurrent disease have reported few cases of objective tumor regression, tumors tended to remain stable without the appearance of new metastatic foci. 15,[17][18][19][20]35 This suggests that NKT cell activation therapy might be more effective at targeting metastatic disease than primary tumors. Since primary breast cancer tumors are effectively treated by surgical resection, and disseminated metastasis remains the primary cause of mortality, 50 NKT cell activation therapy presents a promising therapeutic avenue.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Preclinical and clinical studies have shown that NKT cell activation with exogenous glycolipids provides significant protection from tumor progression. [15][16][17][18][19][20] Although several studies have examined the role of NKT cell activation on primary mammary carcinoma growth, 21,22 the potential therapeutic benefits of NKT cell activation in metastatic breast cancer have not been explored in detail. The aim of this work was to examine the role of NKT cell activation in a postsurgical breast cancer metastasis model.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical and functional iNKT cell deficiencies have been reported in a number of human diseases [189][190][191][192]. These findings led to clinical trials in humans for cancer involving the adoptive transfer of ex vivo expanded autologous DC, pulsed with a-GC, in the absence or presence of expanded iNKT cells [193][194][195]. Although these treatments were well-tolerated and resulted in the generation of antitumor CD4 + and CD8 + T cell responses, clinical responses have been limited and future refinements are required to optimize the generation of efficient antitumor immunity.…”
Section: Other Unconventional T Cells Bridging Innate and Adaptive Immentioning
confidence: 99%
“…Even more, other unconventional T cell subsets may drive similar reactions, albeit in response to different stimuli and in different anatomical contexts, arguing for a general role of innate T cell subsets as natural adjuvants to promote protective immune responses. In analogy to the exploitation of iNKT cells in the clinic [193][194][195]223,224], approaches specifically targeting Vc9/Vd2 T cells may have a similar potential as vaccine adjuvant, to boost immune responses against pathogens and tumors and to modulate autoimmune responses.…”
Section: Innate Regulation Of Adaptive Immune Responses: Vd2 + Versusmentioning
confidence: 99%
“…The expanded NKT cells were able to lyse glioma cells, which retained expression of CD1d. Adoptive transfer of autologous NKT cells activated in vitro with ␣GalCer and IL-2 was also tested in a phase I clinical trial in cancer patients (73). However, none of these clinical trials to date has succeeded in achieving significant efficacy against human tumors in vivo, in contrast to the studies in mice.…”
Section: Type I Nkt Cells In Tumor Immunity and Immune Regulationmentioning
confidence: 99%